Migrasi simbolik wacana kuasa tubuh: menguak wacana tubuh dalam Ode untuk Leopold Von Sacher-Masoch karya Dinar Rahayu - Ida Nurul Chasanah (Faculty of Social and Political Science, Universitas Airlangga, 2014)
The presence of Indonesian women writers with the dominant discourse of the power of body, presenting the pros and cons that would not go over. Female body is the language of women that can be poured through the writing of literary works. Helene Cixous brought the spirit of